Potato hydroponical production in different concentrations of nutrient solution and growing seasons - Muller, Douglas Renato; Bisognin, Dilson Antônio; Andriolo, Jerônimo Luiz; Dellai, Jacso; Copetti, Francis (Pesquisa Agropecuaria Brasileira, 2007)
The objectives of this work were to evaluate photosynthetic efficiency and hydroponic production of potato minitubers, in different concentrations of nutrient solution and growing seasons. The experiment was carried out inside a screenhouse, in a closed hydroponic system with sand as growing media, during fall and spring of 2005. The nutrient solution concentrations of 0.5, 1, 1.5, 2 and 2.5 dS m-1 were compared as treatments, in a completely randomized experimental design, with three replications. Total, shoot and tuber dry mass, tuber fresh weight and number, photosynthetic efficiency and indexes of leaf area and harvest were determined. Tuber yield is not affected by reducing nutrient solution concentration in a closed hydroponic system, with sand as growing media. Photosynthetic efficiency is maximized during spring growing season and depends upon nutrient solution concentration.